Development of Learning Mindset Scale in Senior High School Students: Pengembangan Skala Mindset Belajar Pada Siswa Sekolah Menengah Atas - Lestari, Veranika Dwi; Azzahra, Fatimah (Prosiding University Research Colloquium, 2024)
Developing a learning mindset scale for high school students is important to measure learning mindsets and provide insight for educators in increasing students' motivation and learning success. In learning, Dweck stated that there are two types of mindset, namely fixed mindset as a fixed mindset and growth mindset as a developing mindset. This research aims to overcome the lack of research and development of measuring tools related to mindset, as well as helping individuals find out what type of learning mindset they have. The research method includes four stages: confirming the measuring area, writing items, testing the scale, and testing psychometric properties. Participants consisted of 112 SMA/MA students aged 15-18 years, with data collection via online methods (92 respondents) and face-to-face (20 respondents). The research results showed the validity of relevant content on 67 items with Aiken's V > 0.80, good readability with positive feedback, and produced two independent scales, namely: the Growth Mindset Scale and the Fixed Mindset Scale. The Growth Mindset Scale has 54 final items with a Cronbach's coefficient ? = 0.954 and the Fixed Mindset Scale has 49 final items with a Cronbach's coefficient ? = 0.953. It can be concluded that the Learning Mindset Scale is divided into two independent scales with good reliability.